Journey to Motherhood in the First Year After Child Birth - Nahid Javadifar; Fereshteh Majlesi; Alireza Nikbakht; Saharnaz Nedjat; Ali Montazeri (Tehran University of Medical Sciences, 2016)
Objective: Child bearing is a period of psychological challenges that must be viewed in a social context. This study reports the maternal transition from the perspective of Iranian first-time mothers in the first year after childbirth. Materials and methods: Qualitative method was chosen for explanation of mothers' individual experiences of motherhood.26 first-time mothers (aged 18-35 years old with various socio-economic status) who had delivered between 0-1 year prior to the interviews participated in the study.Data were collected through in-depth semi-structured interviews and interview transcripts were analyzed using the constant comparison method. Results: The core category was called "Regaining advanced balance." There were several themes within this category: "internal conflicts", "encounter and interaction" and "internalization". They felt unpreparedness, lack of control over their lives, incomplete maternal feelings and unstable relation to their husbands and others. Within the first postpartum days and weeks a sort of attachment develops between mother and child as the mother starts to attain a better understanding of maternal feelings; she begins to accept the child as an independent identity and reconstructs herself. As the attachment to child deepens, the mother feels control over the affairs. She realizes a kind of development and integration in herself which specifically stems from becoming a mother and attempts to strengthen family bonds. Conclusion: Through the expression of new mothers' experiences toward motherhood, healthcare providers can reach a better perception of the emotional and psychological changes as well as the various aspects of mothers' acceptance of their maternal role and helps a better preparation and presentation of effective training programs for mothers and families.